Learner proficiency and focus on form during collaborative dialogue - Leeser, Michael J. (Language teaching research : LTR, 2004)
One of the challenges in content-based instruction in second language classrooms is how to focus on form in a way that is both effective and appropriate. The use of collaborative tasks that push learners to consciously reflect on their own language use (i.e., produce ‘language-related episodes’) while conveying meaning has been proposed as one way to accomplish this goal. Studies investigating the use of collaborative tasks that encourage learners to produce language-related episodes (LREs) have been shown to affect positively L2 development. However, little is known about how the proficiency of each dyad member affects how and how much dyads produce LREs during collaborative tasks. Therefore, the study reported in this article investigated how grouping learners by their relative proficiency (high-high, high-low, or low-low) affected the amount, type (lexical or grammatical) and outcome (correct, unresolved, or incorrect) of LREs produced during a passage reconstruction task, completed by twenty-one pairs of adult L2 Spanish learners from a content-based course. The findings revealed that the proficiency of the dyad members affected how much the dyads focused on form, the types of forms they focused on as well as how successful they were at resolving the language problems they encountered.